Dislipidemia na infância: Uma revisão de literatura - Gabriela de Lima Carlesso; Gabriel Zampirolli Azevedo; Bárbara Silva Ton; Tami Guerreiro Estevam Vieira; Marcella Calazans Reblin de-Oliveira; Gustavo Carreiro Pinasco (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: To describe the state of the art in the assessment and management of pediatric patients with dyslipidemia. METHODS: The review was carried out using the PubMed database, taking into account articles published between 2005 and 2021. The publications were selected based on the keywords: "dyslipidemia AND (treatment OR screening OR diagnosis) NOT adult" and those articles that strayed from the topic were excluded. RESULTS: Dyslipidemia is a growing concern in pediatrics, characterized by changes in lipid metabolism, leading to an increased cardiovascular risk. It can be classified as primary or secondary according to its etiology. Among the primary etiologies, familial hypercholesterolemia (FH) is highlighted due to its severity, leading to early cardiovascular outcomes. Universal screening for dyslipidemia should be performed in children aged 9-11 years and 17-21 years, and selective screening in children aged 2-8 years and 12-16 years. In addition to lifestyle changes, such as diet and physical exercise, the first-line drug treatment is based on the prescription of statins, with a more aggressive treatment being required in cases of FH, which needs the association of ezetimibe and an earlier prescription of LDL-apheresis. The most critical cases should be referred to a specialist. Periodic follow-up should be performed with lipid profile and laboratory and imaging tests to rule out possible side effects of medications. CONCLUSIONS: The approach to dyslipidemias is still a very controversial topic. Longer cohort studies are needed to assess the long-term effect of drug therapies on cardiovascular risk in adulthood.